JOB MARKET INFORMATION SYSTEM USING EXTREME PROGRAMMING - Sirait, Agustian William Soen; Pinontoan, Benny; Kalengkongan, Wisard Widsli; Ketaren, Eliasta (STMIK TIME, 2025)
This study presents the development of a web-based job vacancy portal aimed at streamlining employment information access for job seekers and employers. Using the Extreme Programming (XP) methodology, the system was built iteratively with frequent stakeholder feedback to ensure agility and adaptability. The research involved requirement gathering through interviews and observations, followed by designing, coding, and testing cycles. The system features user registration, job posting, search functionalities, and admin management. The results indicate that XP enhanced collaboration, reduced development risks, and delivered a system that meets user needs effectively.